Nesting biology of the leafcutting bee Megachile (Pseudocentron) gomphrenoides (Hymenoptera: Megachilidae) in an agro-ecosystem - Torretta, Juan Pablo (2012)
The nesting biology of the leafcutting bee Megachile (Pseudocentron) gomphrenoides Vachal (Hymenoptera: Megachilidae) was studied in an agro-ecosystem in the Province of Buenos Aires, Argentina. Data were obtained from trap-nests placed in the field margin during two agricultural years (2008/2009 and 2009/2010). Females made an average of 7.55 cells per nest, and used leaves of at least three plant species to build their nests. Provisions of cells were principally of Asteraceae pollen. Adult emergence showed a bimodal pattern suggesting a facultative bivoltinism life cycle. Approximately, 30 % of all offspring failed to complete development to the adult stage and an additional 10 % were killed by natural enemies. These included parasitic wasps (Eulophidae: Melittobia and Horismenus), a cleptoparasite bee (Megachilidae: Coelioxys), and a bristle beetle (Meloidae: Tetraonyx). The host/cleptoparasite association between M. gomphrenoides and Coelioxys remissa constitutes the first such record for both species, and the Megachile–Tetraonyx interaction was previously unknown. M. gomphrenoides possesses some characteristics that make it an interesting potential opportunity to use this species for pollination of commercial sunflowers in the Pampean region.